Operation scheduling of a coal-fired CHP station integrated with power-to-heat devices with detail CHP unit models by particle swarm optimization algorithm - Liu, Ming; Wang, Shan; Yan, Junjie (Energy (Oxford), 2021)
The accommodation of high-penetration renewable power poses a considerable challenge to power grids. Coal-fired combined heat and power (CHP) stations are forced to enhance their operational flexibility by applying heat-power decoupling technologies. Power-to-heat devices, including electric boilers and heat pumps, are capable to enhance the operational flexibility of coal-fired CHP stations. The problem regarding the operation scheduling of a CHP station with multiple CHP units and power-to-heat devices is addressed in this study. Operation optimization models integrated with detail CHP unit models are developed, and the particle swarm optimization algorithm is utilized as the optimization algorithm. Then, a case study are carried out. Results show that the unequal distribution of heating and power loads among coal-fired CHP units can decrease the total irreversibility caused by heating steam pressure regulation. The operation scheduling method provided in this study can decrease the total coal consumption by 14.14 and 14.70 t/day for the CHP station integrated with an electric boiler and a heat pump, respectively. As a result, 1204.7 and 1252.44 ton CO2, and an additional ∼182 and ∼190 kUSD/year can be saved for the reference CHP station integrated with an electric boiler and a heat pump, respectively. •Power to heat devices are applied to achieve heat-power decoupling of CHP station.•Operation optimization models integrated with detail CHP unit models were developed.•Energy consumption characteristics within the operation domain are obtained.•Total exergy destruction is decreased by heat and power load distribution.•Over 180 kUSD/year can be saved by the proposed operation scheduling strategy.